PROTECTING THE AUTONOMY OF PATIENTS AT THE END OF LIFE IN THE MEDICAL RELATIONSHIP IN CHINA - WU, Tao (MEDECINE LEGALE DROIT MEDICAL, 2025)
The expected survival time of patients at the end of life is short and they are often in an unconscious state. These elements make the exercise and the rotection of autonomy of these patients more complex and difficult compared to other patients. Existing Chinese legislation and clinical practice provide three measures for patients at the end of life who cannot express informed consent to exercise autonomy: advance medical directive, delegated autonomy for the patient’s relatives, and decision-making by medical institutions on their behalf. Because of the traditional Chinese culture and the complexity of contemporary social development, the efficiency of these three approaches is still unclear. The reflection conducted for the preparation of this presentation showed that it would be necessary to strengthen the legal validity of the legislation for advance medical directive. At the same time, the intervention of health care professionals, especially the physician, remains essential to safeguard against arbitrary and inappropriate medical decisions when exercising medical autonomy for patients at the end of life.